Konsepsi Bimbingan dan Konseling Untuk Pernikahan dan Keluarga Islami - Mohammad Fatih Luthfi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2018)
Guidance and counseling (BK) is a service needed by modern society in helping someone to get out of the problem (to solve problem), both students in school and other individual in society. BK service based on Islamic world view becomes a prospective new treasury and has the potential to answer the problem of modern society life. BK service sector began to be developed, which initially include: 1) development of personal life, 2) development of social life , 3) development of learning ability, and career development. Meet the needs of the community is now developed the development field 5) family life and 6) the development of religious life. The concept of BK marriage and Islamic families have a goal for married and woven marriages that meet the sharia of God and achieve the happiness of life in the world and in akhirat.Konselor can develop and implements an Islamic approach to counseling, while adhering to professional principles, good character values, and understanding Islamic teachings on marriage and married life so that assisted individuals can attain a sakinah family, mawaddah wa rahmah, peace and prosperity in the pleasure of Allah swt.